Time trend of overweight and obesity in adults from Rio Branco, Acre, Western Brazilian Amazon (2006–2020) - Dias, Flávia Santos Batista; Lima, Yara de Moura Magalhães; Martins, Fernanda Andrade; Silva-Nunes, Mônica da; Andrade, Andréia Moreira de; Ramalho, Alanderson Alves (Universidade Federal de São Carlos, 2022)
Abstract: This study aimed to analyze overweight trend and obesity in adults from Rio Branco, Acre, Western Brazilian Amazon, from 2006 to 2020. This is a time series study, with data from Surveillance System for Risk and Protective Factors for Chronic Diseases by Telephone Survey (VIGITEL). To estimate annual percentage change (APC) and 95% confidence intervals, the software Jointpoint Regression Analysis v.4.6.0.0., was used. In Rio Branco, overweight prevalence ranged from 44.0% in 2006 to 58.9% in 2020, with a bigger frequency among men than that among women. Obesity prevalence has increased from 12.5% in 2006 to 21.4% in 2020, similar between both sexes. From 2006 to 2020, overweight APC was 5.2% (95% CI: 1.4; 9.1) by 2010, and decreased to 1.3% by 2020. Public policies to control obesity and its risks must be both, implemented as strengthen
Keywords: Obesity; Overweight; Nutrition surveys; Epidemiological surveys; Time series studies; CIENCIAS DA SAUDE::NUTRICAO::ANALISE NUTRICIONAL DE POPULACAO